Ilmu Pengetahuan dan Teknologi Bagi Masyarakat Pada POS Pendidikan Anak Usia Dini (PAUD) - Muhammad Busyro Karim; Siti Fadjryana Fitroh (LPPM Universitas Trunojoyo Madura, 2018)
Pos TPAI Bermain dan Belajar Imamul Kholil and Pos Taman PAUD Melati that are Pos PAUD located at RW 007, Banyuajuh Village on Kamal District. Both Pos PAUD aforementioned are declared on the initiative of citizens who care about the presence of children who are unable to attend school at PAUD level. Both partners have the same problems, especially the incomplete operational licenses of the institution, the unorganized management of the institution and the unstructured learning plan. The proposer provides advice on problem solving through the activity of mentoring and counseling of the institution. Based on the situation analysis of the existence of Pos PAUD in Banyuajuh, the operational license of the institution has not been officially processed. The result of agreement with the manager of partner institution, the management will be facilitated by the assistance and guidance of the proposer team in some stages. Based on the initial coordination results, the implementation team prepares the training material by taking into account the institution’s proposal or as required by the institution. In addition to preparing the materials, the team also conducted briefing to students and teams of facilitators to alleviate the implementation of the training. The materials provided in the training are the preparation of the lesson plan, the management of the institution and the producing of teaching media from the used materials. During the training process, the team has monitored and interviewed the trainees regarding the materials, methods and presenters in this activity. Generally, the teachers stated the training was very excellent and the material provided was indispensable material in early childhood learning and management.